The Effectiveness of The Traditional Game Congklak in Developing Children's Cognitiveness at Kindergarten - Alvisari, Deska; Lah, Yahya Che; Tun, HtetMyat (Journal of Basic Education Research, 2023)
Purpose of the study: The aim of this research is to facilitate children's cognitive development by utilizing the traditional Congklak game. The objective is to introduce number concepts and enhance counting skills through engaging with the Congklak game. Methodology: This study employed a quantitative research approach with an experimental design to assess the impact of the traditional Congklak game on the cognitive skills of kindergarten children. Data collection involved participant observation during Congklak game sessions integrated into the learning process. Quantitative statistical techniques were utilized for data analysis to determine significant differences between the experimental and control groups. Main Findings: The findings of this study demonstrate that children who engaged in the traditional Congklak game showed significant improvements in their cognitive skills, particularly in numeracy and analytical abilities. The data also revealed a positive impact on the concentration levels of children who participated in the Congklak intervention, highlighting the potential of traditional games as effective learning tools at the kindergarten level. Novelty/Originality of this study: The novelty of this research lies in its focus on the traditional Congklak game as a tool for enhancing children's cognitive development at the kindergarten level. This study contributes to the existing body of knowledge by exploring the specific and targeted impact of Congklak on early childhood learning. Furthermore, this research incorporates cultural aspects and local values inherent in the game, enriching the early childhood educational experience.